Peculiarities of ecological cartography of the black sea - Білявський, Г.О; Голод, А.В. (Proceedings of National Aviation University (archive), 2010)
Article is devoted to meaningfulness estimation of ecological cartography of sea aquatory in forming ecological conditions in regions of the Black Sea. Estimation of pollution degree of sea regions environment considered. The regions the most unhappy in ecological attitude are defined.